Future of water recycling: A review of the direct potable water reuse - Aleksić Natalija; Šušteršič Vanja (Reciklaža i Održivi Razvoj, 2022)
Population growth, increasing water stress, and water scarcity have influenced the consideration of the reuse of treated wastewater as a possible alternative water source. Currently, recycled water is mainly used in industry, agriculture, and landscape irrigation, and now, in certain parts of the world, recycled water is also used as drinking water due to the limited freshwater resources. To meet the future water supply needs, the direct potable water reuse could be studied as an alternative source of drinking water. Direct potable reuse can enhance sustainability and water supply reliability. This paper analyzes direct potable water reuse as a circular principle in water sector and compares several successful cases of direct potable water reuse in Namibia, South Africa, Texas and New Mexico. Countries that use direct potable reuse are successful examples of using wastewater to form sustainable and reliable water supplies, which is of great significance for the future.